2016
DOI: 10.1108/jeee-03-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

University students’ entrepreneurial tendency in China

Abstract: Purpose – This paper aims to explore the impact mechanism of Chinese university students’ perceived entrepreneurial environment on their entrepreneurial tendency in the context of Chinese economic transition. In particular, the paper provides a reference for relevant departments to make policies and entrepreneurship educators to perfect the pedagogical design and curriculum development in entrepreneurship education programs. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 52 publications
1
16
0
1
Order By: Relevance
“…Few researchers have explored the relationship between the perception of the entrepreneurial environment and individuals' entrepreneurial motivations. For instance, Yao et al (2016) discovered that college students' entrepreneurial motivations are affected by their perceptions of the socio-economic environment. Nam and Hwansoo (2019) indicated that entrepreneurs' attitudes and motivations are significantly affected by their perceptions of the entrepreneurial environment.…”
Section: Perception Of Entrepreneurial Environment and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Few researchers have explored the relationship between the perception of the entrepreneurial environment and individuals' entrepreneurial motivations. For instance, Yao et al (2016) discovered that college students' entrepreneurial motivations are affected by their perceptions of the socio-economic environment. Nam and Hwansoo (2019) indicated that entrepreneurs' attitudes and motivations are significantly affected by their perceptions of the entrepreneurial environment.…”
Section: Perception Of Entrepreneurial Environment and Motivationmentioning
confidence: 99%
“…Government policies that are favorable to entrepreneurship give rise to more entrepreneurial opportunities and promote the realization of entrepreneurial behaviors (Wu et al, 2018). While policy support offers college students a certain level of protection, preferential entrepreneurship policies can incentivize more latent entrepreneurs (Yao et al, 2016). Nam and Hwansoo (2019) found that the accessibility of government policies affects entrepreneurs'…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…China has formulated a number of entrepreneurial policies on tax incentives, low interest rates, etc., encouraging student entrepreneurship. Obviously, the current environment in China is suitable for student entrepreneurship (Yao, Wu & Long, 2016). Generally, entrepreneurial education at universities can inform and motivate students, and therefore indirectly increase their willingness to consider entrepreneurship a career path (Lange et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…thus encouraging student entrepreneurship. It is obvious that the current environment in China is suitable for student entrepreneurship (Yao, Wu & Long, 2016). In general, entrepreneurship education at the universities can inform and motivate students, and therefore increase their willingness to consider entrepreneurship as a career path (Lange, Marr, Jawahar, Yong & Bygrave, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%